2 Promoting resilient and sustainable health and food systems. (18th October 2022) - De-Regil, Luz Maria; Lima do Vale, Marjorie Rafaela; Mahy, Lina; Rao, Nitya; Andriamahefalison, Narindra; Crew, Sterling; Johnsen, Jørgen T; Collins, Jorja; Haldane, Victoria; Bradfield, James; Nabarro, David
Abstract : Food systems are a complex web of actors and activities involved from farm to fork on aspects of food production, processing, distribution, preparation, consumption and ultimately the management of food waste. Food systems and the choices made by food system actors are contributing to detrimental impacts on animal, human and planetary health including losses in biodiversity, exhaustion of natural resources, zoonoses, foodborne illness and occupational hazards ( figure 1 ). Current food systems are also failing to protect individuals' and communities' food security, good nutrition, and health. Health systems also have an impact on climate change and natural resources degradation. For instance, if health systems were a country it would rank among the top 5 in terms of carbon emissions, with an estimated contribution of 4.4%. Research has shown that there is an appetite to connect and transform food and health systems. For example, hospital settings can consider the use of locally grown foods, offer plant-based meals, use water and energy-saving kitchens and divert food waste from landfill. Realizing these activities can be achieved through policy action by making changes in legislation, by ensuring organisational culture and leadership, and by creating networks and champions for environmentally sustainable practices in health system settings. There is also an opportunity to integrate environmental sustainability in health systems teaching and research. Lessons from fighting the Covid-19 pandemic could be applied towards reducing food and health system impacts on climate, such as i) developing a clear understanding of the problem, of potentially effective solutions and identifying those interests are being prioritised, ii) start tackling the problem from areas making the largest contributions or being affected the most, and iii) knowing that shifting people's behaviour is at the core of any solution. Transformed food and health systems must be contextually relevant, resilient, regenerative, empowering, and with health at their centre. Bold government, community, and business actions that promote interdisciplinarity, collaboration and capacity building are key aspects to be considered.